Improving the Skills of Posyandu Cadres in Processing Nipah Fruit into Nutrient-Rich Functional Foods to Prevent Stunting in Katapiang Village, Batang Anai District, Padang Pariaman Regency - Iryani, Iryani; Iswendi, Iswendi; Kurniawati, Desy; Amelia, Fitri; Suryani, Okta; Parbuntari, Hesty; MAIDA, MARGARITA CLAUDYA; Rivaldo, Ifan (Pelita Eksakta, 2025)
Stunting remains a major public health issue in Indonesia, including in Padang Pariaman Regency, where the prevalence reached 28.3% in 2021 and declined to 19.4% in 2023. Efforts to prevent stunting require a community-based approach that utilizes local resources, one of which is the nipa palm fruit (Nypa fruticans), known for its high nutritional content and potential as functional food. This Community Service Program (PKM) aimed to enhance the knowledge and skills of Posyandu cadres in Nagari Katapiang in processing nipa fruit into nutritious and economically valuable food products. The methods included nutrition education, dissemination of information on nipa fruit potential, and training on appropriate technology for processing nipa into food products such as jam, nuggets, and meatballs. Evaluation was carried out through pre- and post-activity questionnaires. The results showed a significant increase in cadres’ knowledge of nipa’s nutritional content (from 20% to 100%) and health benefits (from 30% to 100%). Perceptions of nipa’s role in stunting prevention also increased from 25% to 95%. Furthermore, practical skills in producing nipa jam improved, where all participants who had never tried before were able to produce processed products after the training. Thus, this PKM activity successfully enhanced the knowledge and practical skills of Posyandu cadres, while demonstrating the potential of nipa fruit as a local food innovation supporting stunting prevention efforts.